Etnoparenting: Pengasuhan Anak Usia Dini Berbasis Budaya Sunda - Eti Nurhayati; Ina Anisan Napisah; Suci Ramdaeni (Institut Agama Islam Negeri Madura, 2024)
Child care carried out by parents in Indonesia in each region has different characteristics. The aim of this research is to find out early childhood care based on Sundanese culture, especially in Ciroke Majalengka village. A type of semi-ethnographic qualitative research where the researcher carries out participant observation, in-depth interviews, and documentation. The informants in this research were community leaders, paraji, and parents who were involved in parenting traditions. The data obtained was explained using a grounded theory approach. The results of this research are: (1) The parenting traditions in Ciroke village which include: babarit, digedog, nurunkeun, gusaran, radinan, and circumcision are still preserved today. (2) Cultural values ​​in this tradition include: trust in elders, religious values, politeness, mutual cooperation, and friendship. (3) The impact of these cultural values ​​includes: the involvement of the father and mother's role in parenting (shared parenting), the character of education, and the implementation of parental policies, thus forming good gender behavior and relationships in children.